2017
DOI: 10.1002/cncr.30983
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the use of active surveillance for low‐risk prostate cancer

Abstract: BACKGROUND: This study assessed the use of active surveillance in men with low-risk prostate cancer and evaluated institutional factors associated with the receipt of active surveillance. METHODS: A retrospective, hospital-based cohort of 115,208 men with lowrisk prostate cancer diagnosed between 2010 and 2014 was used. Multivariate and mixed effects models were used to examine variation and factors associated with active surveillance. RESULTS: During the study period, the use of active surveillance increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 46 publications
(109 reference statements)
2
23
1
Order By: Relevance
“…However, approximately 57% of incident prostate cancer cases occur in this age group 26 and Medicare aged patients are often included in other active surveillance studies. 9, 11 Additionally, as Medicare data does not include cancer grade or stage, our analyses are presented in the context of all men with newly diagnosed prostate cancer and among all men without pre-existing prostate cancer; we cannot comment on active surveillance use in specific risk categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, approximately 57% of incident prostate cancer cases occur in this age group 26 and Medicare aged patients are often included in other active surveillance studies. 9, 11 Additionally, as Medicare data does not include cancer grade or stage, our analyses are presented in the context of all men with newly diagnosed prostate cancer and among all men without pre-existing prostate cancer; we cannot comment on active surveillance use in specific risk categories.…”
Section: Discussionmentioning
confidence: 99%
“…9, 10 Further, the use of active surveillance varies considerably, even among men with low-risk prostate cancer. 11 To elucidate these findings, large population-based studies using claims data are needed. While clinical registries generally have high-quality data, they often include highly selected practices or those participating in quality improvement efforts.…”
Section: Introductionmentioning
confidence: 99%
“…13 There were studies that have demonstrated that the low-risk PCa (L-PCa) achieved the giant benefit from active surveillance and its incidence of recurrence was less than 25% at 5 years post treatment. 5,[14][15][16][17] Therefore, it is also quite important to rationally use this application for clinicopathological assessment prior to biopsy in patients with risk of PCa. However, at present, most studies only focused on the model of predicting PCa or HG-PCa.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation from America has stated that only 4-20% of patients that met the standards of active surveillance were willing to select the treatment of active surveillance, which due to the limitations of existent predictive methods and the patients' uncertainty about their disease progression. [15][16][17][18] Now, patients can use the PCCRC to selfassess the changes of PCa risk conveniently. During the follow-up, if the results of the self-assessment continue to worsen, he should go to the hospital for further assistant.…”
Section: Discussionmentioning
confidence: 99%
“…While over-treating low-risk patients has been an identified issue, active surveillance has been an increasingly preferred option for men diagnosed with low-risk prostate cancer [18]. Active surveillance is a conservative management technique of periodically observing PSA levels and biopsies, to monitor disease progression of low-risk neoplasms [25]. This technique prevents unnecessary treatment and treatment-related morbidities of prostate cancer with no metastatic potential [26].…”
Section: Discussionmentioning
confidence: 99%